Bioenergy and Bioresources Usage in the Context of Circular Economy Promotion - Melnyk, Leonid; Kubatko, Oleksandr; Fedyna, Svitlana; Torba, Ivan (Economics and Business, 2021)
The circular economy, which minimises the level of environmental pollution, creates a promising background for sustainable development. The application of bioeconomics principles provides the use of by-products of agriculture, forestry, food waste, and wastewater as raw materials for electricity and heat. The objective is to analyse the prerequisites for bioenergy development as one of the circular economy areas. FGLS estimations are performed over the period of 2007–2018. The leading position in terms of bioenergy sphere growth is occupied by the European Union, followed by the countries of Asia and North America. The division of biomass into “traditional” and “modern” is discussed, where traditional biomass is mostly used for cooking and space heating in developing countries, while the EU is focusing on the development of second-generation (2G) biofuels when the biofuel is produced from non-food raw materials. It is estimated that the annual production of energy from renewable sources is about 225 thousand tons of o. e. in Ukraine. It is found that the legal field and the strategic directions of the bioeconomy in the European Union and Ukraine coincide, but the pace of development of bioenergy in Ukraine can be described as very slow. To increase the bioenergy potential, it is recommended to apply green tariffs, renewable energy certificates, and subsidies to energy producers.